Spermine Enhances the Peroxidase Activities of Multimeric Antiparallel G-quadruplex DNAzymes - Raphael I. Adeoye; Theresia K. Ralebitso-Senior; Amanda Boddis; Amanda J. Reid; Francesca Giuntini; Amos A. Fatokun; Andrew K. Powell; Adaoha Ihekwaba-Ndibe; Sylvia O. Malomo; Femi J. Olorunniji (Biosensors)
G-quadruplex (G4) DNAzymes with peroxidase activities hold potential for applications in biosensing. While these nanozymes are easy to assemble, they are not as efficient as natural peroxidase enzymes. Several approaches are being used to better understand the structural basis of their reaction mechanisms, with a view to designing constructs with improved catalytic activities. Spermine alters the structures and enhances the activities of some G4 DNAzymes. The reported effect of spermine in shifting the conformation of some G4 DNAzymes from antiparallel to parallel has not been tested on multimeric G4 DNAzymes. In this study, we examined the effects of spermine on the catalytic activities of multivalent constructs of Bcl2, c-MYC, PS2.M, and PS5.M. Our findings show that spermine significantly improved the peroxidase activity of PS2.M, an antiparallel G4 DNAzyme, while there was no significant effect on c-MYC, which already exists in a parallel conformation. The addition of spermine led to a substantial increase in the initial velocity of PS2.M and its multimeric form, enhancing it by approximately twofold. Therefore, spermine enhancement offers promise in expanding the range of DNAzymes available for use as biosensing tools.